2022
DOI: 10.1038/s42003-022-03543-1
|View full text |Cite
|
Sign up to set email alerts
|

Anchor-based bisulfite sequencing determines genome-wide DNA methylation

Abstract: Whole Genome Bisulfite Sequencing (WGBS) is the current standard for DNA methylation profiling. However, this approach is costly as it requires sequencing coverage over the entire genome. Here we introduce Anchor-Based Bisulfite Sequencing (ABBS). ABBS captures accurate DNA methylation information in Escherichia coli and mammals, while requiring up to 10 times fewer sequencing reads than WGBS. ABBS interrogates the entire genome and is not restricted to the CpG islands assayed by methods like Reduced Represent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 24 publications
0
5
0
Order By: Relevance
“…WGBS is the current ideal for DNA methylation analysis, as it provides high-resolution, single-based methylation maps [ 20 ], which enable non-CpG methylation in mammals to be fully understood. Previous studies have suggested that non-CpG methylation is more abundant in stem cells than in differentiated cell types.…”
Section: Discussionmentioning
confidence: 99%
“…WGBS is the current ideal for DNA methylation analysis, as it provides high-resolution, single-based methylation maps [ 20 ], which enable non-CpG methylation in mammals to be fully understood. Previous studies have suggested that non-CpG methylation is more abundant in stem cells than in differentiated cell types.…”
Section: Discussionmentioning
confidence: 99%
“…It is possible that the technical and economic requirements for RRBS or WGBS will soon become lower and more affordable in routine clinical practice. Other approaches could be used, such as anchor-based bisulfite sequencing (ABBS) [ 45 ] and nanopore sequencing [ 46 ].…”
Section: Discussionmentioning
confidence: 99%
“…Notably, the application of GLORI is limited by its relatively high cost as a higher sequencing depth is required compared to enrichment‐based methods. This disadvantage could potentially be mitigated in future improvements by learning from the bisulfite sequencing field, where the development of reduced representation bisulfite sequencing [124] and anchor‐based bisulfite sequencing [125] significantly reduced sequencing cost while preserving a reasonable coverage of the DNA methylome.…”
Section: Special Applications Of M6a‐sequencing Methodsmentioning
confidence: 99%